INTERLEUKIN-18 LEVELS IN SCHIZOPHRENIA PATIENTS RECEIVING ANTI-PSYCHOTIC THERAPY AT THE PSYCHIATRIC POLYCLINIC OF SITI RAHMAH ISLAMIC HOSPITAL - Hasni, Dita; Anggraini, Debie; Anissa, Mutiara (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
The use of antipsychotic therapy is effective in managing symptoms and has become a cornerstone in the treatment of patients with schizophrenia. However, antipsychotics have side effects on the immune system, particularly affecting Interleukin 18 (IL-18) levels. Therefore, it is important to assess IL-18 levels in schizophrenic patients receiving antipsychotic therapy. Objective: To determine IL-18 levels in schizophrenic patients undergoing antipsychotic therapy and receiving outpatient care at the RSI Siti Rahmah Padang clinic. This descriptive study recruited 25 schizophrenic patients receiving antipsychotic therapy who voluntarily participated. IL-18 levels were measured using the ELISA method from patient serum. Results: In 25 schizophrenia patients who received antipsychotic therapy, IL 18 levels were obtained as much as 483.7 SD ± 27.3 ng/ml. The subjects were aged 36-45 years (60%), 88% were male, and 64% were using atypical antipsychotics. Schizophrenic patients receiving antipsychotic therapy at RSI Siti Rahmah Padang showed elevated IL-18 levels.